Abocanhar tomates: autorretratos em filme instantâneo de uma artista e suas tentativas de gerir o tempo - Borges, Sheryda Lopes (2023)
In this dissertation I discuss my creative process of works with instant film self- portraits made during the period of social isolation due to the Covid-19 pandemic. These are productions closely linked to my relationship with factors such as (self)demand for productivity and procrastination and the use of tools that aim to help maintain focus on tasks, especially the Pomodoro Method. This relationship takes the form of anguish, which was intensified during the pandemic. In this work, Salles (2011) and Ostrower (2004) help me track my creative process while Han (2017), Bauman (2021) and De Masi (2000) help in the process of understanding the social demand for productivity. Along this path, I also observe the way in which my role as a teacher of visual arts and crafts influences my creative process, making it impossible to assign each task to its own time, as it is permeated by and influences the process of the artist/teacher/researcher. Here, Paulo Freire (1996) and Zamboni (2001) bring reflections on aspects of the teacher-researcher and the researcher in art and the nature of their paths. When taking a look at the social constructions of gender and how demands are placed on women, I turn to Scott (1995) and Bourdieu (2005), while Leal (2012) brings the perspective of gender inequality in the field of visual arts . In this way, the process of demanding productivity is more intense for us, women, as we accumulate tasks in the private and public spheres of our lives, which has made the pandemic even more difficult for us. The works I present in this text are an intimate look at my anxieties about these themes and were executed in the limiting context of social isolation. They bring to light a social construction in which individuals are constantly held accountable and led to believe that any failures are their individual fault, when, in fact, the very construction of certain goals is sickening. From a gender perspective, this occurs even more seriously. In addition to the theorists mentioned here, I will present artists such as Frida Kahlo, Val Sousa and Cindy Sherman who influenced my creative path or who, in some way, dialogue with the reflections presented.